High Resolution Active Optical Remote Sensing Observations of Aerosols, Clouds and Aerosol-Cloud Interactions and Their Implication to Climate - Lolli, Simone; Qin, Kai; Campbell, James; Wang, Sheng-Hsiang (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Remote Sensing is of paramount importance for Earth Observation to monitor and analyze the Earth's vital signs. In this Special Issue are reported the latest research results involving active optical remote sensing instruments, both from ground-based to satellite platforms, that are involved in analyzing the vertical and horizontal aerosol and cloud distribution, other than their geometrical, optical and microphysical properties. Those active optical remote sensing techniques are also very useful in determining pollutant dispersion and the dynamics inside the boundary layer. The published studies put in evidence the hidden mechanisms on how pollution from the source is advected transnationally in other countries and the interaction with local meteorology.